PERANCANGAN PROTOTYPE ALAT PENGURANG KADAR AIR PADA MADU KAPASITAS 5 LITER - Achmad Kusairi Samlawi; Wahyu Slamet Pamungkas (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2019)
The quality of Honey must meet the requirements set by the Indonesian National Standard (SNI) in 2004. In the standard set, the enzyme diastase function is at least 3 DN, hydroxymethylfurfural (HMF) maximum 50 mg / kg, maximum air content is 22% b / b, sugar reducing at least 65% b / b,asucrose maximum 5% b / b, acidity maximum 50 milliecivalents / kg, solids not up to maximum 0.50% b / b, maximumAash content 0.50% b / b (BSN), 2004) To meetAthese standards designedAa tool that willAreduce the air content in honey without damaging it as it is vaccinated at -70 -70 bar with temperatures below 40 ° C. With the results of the balance shows: (1) electric motor with power ¼ HP with 1400 rpm rotation. (2) V-belt transmission with large outside pulley dimensions = 231.3 mm, small outer plley = 104 mm. Using a v-belt with no. 44 in / 1118 mm. Horizontal shaft with dimensions of large pulley shaft diameter = 18 mm and small pulley shaft diameter = 15 mm. (3) Using a gearbox damper with a ratio of 1:40. (4) Stirrer shaft with 304 grade stainless steel material with a length of 975 mm and a shaft diameter of 40 mm. (5) Stirrer impeller with six blade impeller type with dimensions of diameter 1667, mm and thickness of 3 mm. (6) Vessels with cylindrical types and having a thickness of 2.5 mm, a diameter of 500 mm and a length of 500 mm. With an ellipsoid head type with dimensions of 520 mm in diameter, 125 mm in height and 2.5 mm in thickness. (7) Frame with a profile of mild steel profile dimension dimensions of 40 mm x 40 mm x 2.5 mm.